2013
DOI: 10.1093/ndt/gft359
|View full text |Cite
|
Sign up to set email alerts
|

LMX1B mutation with residual transcriptional activity as a cause of isolated glomerulopathy

Abstract: This is the first report on LMX1B mutation identified in a patient with NPLRD. Residual transcriptional activity would account for normality of the nails and patella in this case. Genetic and pathological analyses of additional cases would clarify the role of LMX1B in glomerulopathy without systemic symptoms, which, together with nephropathy in NPS, can be designated as 'LMX1B nephropathy'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 23 publications
3
50
2
1
Order By: Relevance
“…This pathological entity is characterized by nephropathy without the typical nail and skeletal malformations as in common presentation of NPS. As the respective mutation still resulted in residual transcriptional activity, the authors suggested that LMX1B haploinsufficiency might be causative for the nephropathy-only phenotype in NPLRD patients [142]. In analogy to this study, the segregation of the same mutation within the LMX1B gene in pedigrees of patients with features of autosomal dominant focal segmental glomerulosclerosis has been described [143].…”
Section: Lmx1bsupporting
confidence: 53%
“…This pathological entity is characterized by nephropathy without the typical nail and skeletal malformations as in common presentation of NPS. As the respective mutation still resulted in residual transcriptional activity, the authors suggested that LMX1B haploinsufficiency might be causative for the nephropathy-only phenotype in NPLRD patients [142]. In analogy to this study, the segregation of the same mutation within the LMX1B gene in pedigrees of patients with features of autosomal dominant focal segmental glomerulosclerosis has been described [143].…”
Section: Lmx1bsupporting
confidence: 53%
“…Two groups have reported the detection of novel missense mutations affecting R246 in the homeodomain of LMX1B in patients with isolated renal disease. In one report a patient with nail-patella-like renal disease was found to have an R246Q mutation that has residual transcription activity [40]. In the other report patients with autosomal dominant focal and segmental glomerular sclerosis either with the same R246Q mutation or with a different mutation affecting the same amino acid, R246P, were described [41].…”
Section: Discussionmentioning
confidence: 99%
“…NPS and glomerulopathy (AD) [69][70][71]144 Mutations associated with an isolated glomerulopathy are located in the homeodomain of LMX1B, possibly disrupting the interaction between LMX1B and (podocyte specific) DNA targets [69][70][71] …”
Section: Lmx1bmentioning
confidence: 99%
“…Finally, different inheritance patterns or mutation types in genes involved in syndromic kidney disease can cause an isolated kidney phenotype at the mild end of the phenotypic spectrum. Examples are mutations in LMX1B, which are associated with nail-patella syndrome (OMIM 161200) but can also cause an isolated glomerulopathy [69][70][71] , and mutations in OCRL1, which cause Lowe oculocerebrorenal syndrome (OMIM 309000), but also cause Dent disease 2 (OMIM 300555) 72 . Another example is provided by FRAS1 and FREM2, in which biallelic truncating mutations cause Fraser syndrome (OMIM 219000).…”
Section: Different Presentations Of the Same Phenotypementioning
confidence: 99%